MARINE AGRO-RESEARCH & EDUCATION CENTER - Theodorus Margareth Milenia; Sidhi Wiguna Teh (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
As a maritime country, most of Indonesia's territory is vast waters, with a sea territorial area wider than its land territory, namely the archipelago 2/3 of the territory in Indonesia is ocean and 1/3 is land. This makes Indonesia one of the countries that has great potential in the marine sector. Indonesia has a wealth of abundant marine natural resources. For several centuries, the centers of economic growth and civilization in the territory of Indonesia have had political and economic power based on marine resources. However, along with the large potential of the sea, various problems also arise, one of which is the problem of plastic waste in the ocean. Therefore, a solution is needed to reduce the accumulation of plastic waste in the sea and the need for optimal processing and utilization of marine resources so that Indonesia becomes a strong maritime country. The program in the Marine Life Agro- Research & Education Center (MAREC) focuses on research & seaweed cultivation for the manufacture of bio-degradable plastics and recreational education that aims to reduce the use of conventional plastics to prevent the accumulation of plastic waste in the sea and maintain marine ecosystem populations, while education The center is a tourist place that serves to attract visitors to the project. This project is integrated and is supporting the Oceanographic Research Center by the Indonesian Institute of Sciences. Keywords : Bio Degradable; Livelihoods; Maritime; Natural Resources; Plastic Waste; Processing; Research; Seaweed; Tourism; Water AbstrakSebagai negara maritim, sebagian besar wilayah Indonesia merupakan perairan yang luas, dengan daerah teritorial lautnya lebih luas daripada daerah teritorial daratnya, yaitu kepulauan 2/3 wilayah di Indonesia berupa lautan dan 1/3 nya berupa daratan. Hal ini menjadikan Indonesia salah satu negara yang memiliki potensi besar di bidang kelautan. Selama beberapa abad, pusat - pusat pertumbuhan ekonomi dan peradaban di wilayah Indonesia memiliki kekuatan politik dan ekonomi dengan berbasis sumber daya laut. Tetapi, seiring dengan besarnya potensi laut juga timbul berbagai permasalahan, salah satunya masalah sampah plastik yang terdapat di lautan. Oleh karena itu, diperlukan solusi untuk mengurangi penumpukan limbah plastik di laut serta perlunya pengolahan dan pemanfaatan sumber daya laut secara optimal agar Indonesia menjadi negara maritim yang kuat. Program dalam Marine Life Agro-Research & Education Center (MAREC) berfokus pada kegiatan riset & budidaya rumput laut untuk pembuatan plastik bio degradable dan edukasi rekreatif yang bertujuan mengurangi penggunaan plastik konvensional untuk mencegah menumpuknya sampah plastik di laut dan menjaga populasi ekosistem laut, sedangkan education center merupakan tempat wisata yang berfungsi untuk menarik pengunjung ke proyek. Proyek ini terintegrasi dan bersifat supporting terhadap Pusat Penelitian Oseanografi oleh Lembaga Ilmu Pengetahuan Indonesia.